Foville Syndrome Due to Pontine Hemorrhage and Pontine Infarct: Case Series - Imran I; Syahrul S; Nurul Fajri (Britain International for Academic Research (BIAR) Publisher, 2021)
Foville Syndrome is a rare clinical feature of stroke or brain hemorrhage. Few cases have been reported worldwide particularly in Asian, Indonesia, Aceh. Patient 1: We report the case of a female 64 years old patient, was admitted in the Neurology Department of Dr. Zainoel Abidin General Hospital, Banda Aceh, Indonesia, for an abrupt onset of right body side weakness two day before admission. That weakness was preceded by acute headaches and rotatory vertigo with vomiting. with hypertension history since 5 years. Physical examination found paralysis of right oculomotor movements with intact response of pupils to light, right trochlear nerve palsy, left ipsilateral facial nerve palsy, and right hemiparesis which constitute of Foville syndrome. The brain CT scan shown in the right pontine hypodensity area is pontine infarct. Etiological investigations done to chronic hypertension. Patient received antiplatelet therapy and control of vascular risk factors for secondary prevention (hypertension theraphy), and physiotherapy as treatment with clinical improvement. And she has been discharge 8 days later. Patient 2: 45-year-old right-handed female, was admitted in the Neurology Department of Dr. Zainoel Abidin General Hospital, Banda Aceh, Indonesia, for an abrupt onset of right body side weakness two day before admission. That weakness was preceded by acute headaches and rotatory vertigo with vomiting. with hypertension history since 5 years. Physical examination found paralysis of right oculomotor movements with intact response of pupils to light, right trochlear nerve palsy, left ipsilateral facial nerve palsy, and right hemiparesis which constitute of Foville syndrome. The brain CT scan shown spontaneous hemorrhage in the left pontine’s. Etiological investigations done to chronic hypertension. Patient received therapy control of vascular risk factors for secondary prevention (hypertension theraphy), and physiotherapy as treatment with clinical improvement. And she has been discharge 10 days later. The diagnosis and management of brainstem stroke bring a considerable burden to the healthcare system, the patient, the family members, and the society at large. The slow increase in the global burden of stroke has been steadily increasing.